A high preoperative serum IL-25 level is a negative prognosis predictor after liver resection for HBV-HCC - Chen, Shao-hua; Wang, Xu (Frontiers in Oncology, 2022)
Objective The aim of this study was to evaluate the association between preoperative IL-25 levels and HBV-HCC patient outcomes following liver surgery. Methods This study enrolled consecutive HCC patients that had undergone liver surgery from 2008 to 2015. Baseline patient clinical properties were assessed to establish predictors of postoperative overall survival and recurrence-free survival (OS and RFS, respectively) following liver resection. In addition, serum IL-25 levels were assessed via ELISA. Results Cox regression analyses revealed IL-25 levels to be independently related to the OS and RFS of 896 HBV-associated HCC patients. An optimal IL-25 cutoff level of 14.9 μg/ml was identified, with 206 patients in this cohort having IL-25 levels above this threshold. Both the OS and RFS of patients with an IL-25 level <14.9 μg/ml were significantly better after liver resection as compared to those of patients with higher preoperative levels of this cytokine (p < 0.05). Cox multivariate regression analyses revealed an IL-25 level ≥ 14.9 μg/L to be an independent predictor of poorer RFS and OS. A combination of IL-25 levels and tumor diameter may be an even more reliable predictor of OS. Conclusions IL-25 levels are independent predictors of postoperative survival within HCC patients undergoing liver resection.